Crimes Of Humanity In Valley Of The Wolves PalestineMovie (2011) Directed By Zubeyr Sasmaz: A Sociological Approach - Ardi R, Anggoro, Drs. Abdillah Nugroho. M. Hum, Drs. Sigit Haryanto, M. Hum (2013)
The probleru oJthit reseqrel? is "l{ew qre tlw orirues of hunqnity reflested. on Crime of Humanity in Valley of the Wolves Palestine (2011) movie by Zubeyr Sasmaz using socialogical approach?. This research is aimed to analyze the structurol elements in Tolley of the Wolves Palestine movie and to describe the crimes of humanity in Valley of the Wolves Palestine movie based on sociological approach. This research is qualitative research besides book and other related references to support the subject matter. The data are taken from text in the form of movie manuscript and also the motion pictures of Valley of the Wolves Palestine. The result of the study found that the sociological aspects of the Valley of the Wolves Palestine movie relates with sociol ssryct on the Yalley of the Wolves Palestine movie is coming from the process of social Islamizqtion in Polestine. Muslim is the most dominont and Jews become the next religion who lives in Pqlestine. The potitieql q peet is thqt Pqlestiniqn Islqruists qnd Seeulqrists qble tq live together where Muslim can get their freedom'.for proy in mosque and everywhere they wants. The culture of Palestine people based on Islam views appears on the movie such as, the dance of art of Muslim when they are praying for Allah and shape of the building. People in Palestine especially people in middle class, who live in a beautifil building fram stone. The religious aspect is that Palestinian people mostly are Muslim and Palestine is a small country where there are also Jews and Christian.